Desulfurisasi Batubara Dengan Metode Leaching Menggunakan Gel Lidah Buaya - Wahyuni, Alfia; Tanjung, Diva Amanda; Hapsauqi, Iqbal; Desmiarti, Reni; Desfitri, Erda Rahmilaila (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Coal is still the world's main energy source, widely used in power generation, steel production materials, cement industry, alumina processing plant paper factories and other chemical industries. Burning coal with high sulfur content produces sulfur dioxide gas (SO2), which can directly or indirectly disrupt the environment and contribute to air pollution and the formation of acid rain. Therefore, desulfurization has become an interesting research topic to improve coal quality. In this research, coal desulfurization is carried out using aloe vera gel as a solvent. 300 ml of aloe vera gel was contacted with 50 grams of coal using a magnetic stirrer with varying stirring speeds of 500 and 750 rpm, for duration 2, 3, 5 and 7 hours. Then, separated, dried, and analyzed for sulfur content, ash content, and calorific value. The results showed that the sulfur content decreased by 19.11% to 24.61%, the ash content decreased by 8.51% to 12.56%, and the calorific value was obtained respectively 6439cal/g, 6381 cal/g, 6433 cal/g, and 6467 cal/g.